Developing the DALAM Model for Active, Deep, and Meaningful LMS-Based Learning - Nurrijal Nurrijal; Suarna Samai (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Digital transformation in education requires learning models that utilize technology not only as a medium for content delivery but also as a means to promote active engagement and meaningful learning. This study aimed to develop the DALAM Digital Flow Model (Deep Active Learning Approach Model) as a Learning Management System (LMS)-based digital learning model integrating the principles of deep learning and active learning. The study employed a Design and Development Research (DDR) approach consisting of needs analysis, goal formulation, model design, model development, and theoretical evaluation.The model was developed through a synthesis of theories on digital learning, LMS, deep learning, and active learning using literature review and content analysis. The resulting DALAM Model consists of five sequential learning phases: Discover, Analyze, Link, Apply, and Meaningful Reflection. These phases are designed to foster conceptual understanding, critical thinking, problem-solving, knowledge application in authentic contexts, and reflective learning. The model also emphasizes active student participation through collaborative and technology-supported learning activities within an LMS environment. In addition to supporting conceptual understanding and problem-solving skills, the DALAM Model is conceptually designed to facilitate self-directed learning, collaboration, communication, digital literacy, and metacognitive awareness. Therefore, the model offers a systematic and innovative framework for designing active, deep, and meaningful digital learning within Learning Management System environments. However, further empirical studies are required to examine its practicality and effectiveness in authentic learning contexts.